The Unique Features of the Development of Sufism in Mavaraunnahr and Khurasan (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2025)
This article reveals the similarities and differences in the development of Sufism in Transoxiana and Khorasan through comparative analysis. In this case, special attention is paid to the period of asceticism, the schools of tariqat, and the stages of systematization of Sufism.